2008
DOI: 10.1007/s11249-008-9384-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Applied Load and Surface Roughness on the Tribological Properties of Ni-Based Superalloys Versus Ta2AlC/Ag or Cr2AlC/Ag Composites

Abstract: The novel Ta 2 AlC-20 vol.% Ag (TaAg) and Cr 2 AlC-20 vol.% Ag (CrAg) composites were tribologically tested versus a Ni-based superalloy Inc718 (SA) by dry sliding at a sliding speed of 1 m/s at room temperature in air at loads from 3 N to 18 N. The TaAg composites were also tested at 8 and 18 N at 550°C, and at a 3 N load against the SA with different surface roughnesses at 26°C and 550°C. At room temperatures, the coefficients of friction, l's, decreased from *0.8-0.9 to *0.3-0.4 for both the TaAg and CrAg c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Attempts have been made to develop wear-resistant composites by incorporating hard particles such as SiC [348], Al 2 O 3 [349,350] or Ag [19,[351][352][353] into the MAX phase matrix. This approach was found to be effective in reducing the wear rate.…”
Section: Tribological Propertiesmentioning
confidence: 99%
“…Attempts have been made to develop wear-resistant composites by incorporating hard particles such as SiC [348], Al 2 O 3 [349,350] or Ag [19,[351][352][353] into the MAX phase matrix. This approach was found to be effective in reducing the wear rate.…”
Section: Tribological Propertiesmentioning
confidence: 99%
“…An exhaustive review was published by Gupta et al, 26 who also performed several investigations. 107,108,109,110 In general at room temperature, the wear rate (WR) was relatively high and almost linearly dependent to sliding distance, meanwhile the initial µ was low (< 0.2) but increased rapidly to larger values (>0.4). Certainly, the tribological response depends on several factors of the microstructure (grain size, purity, porosity, etc), the counter-body (metal, ceramic, hardness, etc), and the testing conditions (temperature, atmosphere, velocities, pressure, lubrication, etc).…”
Section: Tribological Propertiesmentioning
confidence: 99%
“…However, the results reported later in polycrystalline samples have less attractive values. An exhaustive review was published by Gupta et al, 26 who also performed several investigations 107,108,109,110 . In general at room temperature, the wear rate (WR) was relatively high and almost linearly dependent to sliding distance, meanwhile the initial µ was low (< 0.2) but increased rapidly to larger values (>0.4).…”
Section: Mind the Gapmentioning
confidence: 99%
“…In addition, it was found that Cr 2 AlC has an excellent tribological property, especially at elevated temperatures. [28][29][30] The relatively low coefficient and wear rate are attributed to the amorphous or nanocrystalline tribolms form on both contact surfaces. However, to the best of our knowledge, little work focused on the tribological properties of Cr 2 AlC as lubrication additive.…”
Section: Introductionmentioning
confidence: 99%